Mechanical behaviors of rock-like specimens with two non-coplanar fissures subjected to coupled static-dynamic loads. (August 2018) - Feng, Peng; Dai, Feng; Liu, Yi; Du, Hong-bo
Highlights: Conducted the coupled static-dynamic compression tests on fissured synthetic rocks. Revealed the coupled static-dynamic strain rates dependence of the strength and deformation of fissured specimens. Observed different failure modes of fissured specimens under different couple static-dynamic load conditions. Reported the evolution of energy dissipation and release of fissured specimens under different dynamic strain rate and static pre-stress. Abstract: Fissured rocks, widely existing in underground engineering structures, are quite sensitive to coupled static-dynamic loading conditions. Understanding the mechanical properties of fissured rocks under coupled loads is significant for the rational design and stability analysis of underground rock engineering projects. This study experimentally investigated the effect of coupled static-dynamic strain rates on the mechanical behaviors of synthetic rock models containing two non-coplanar fissures. Our results revealed that the mechanical properties of fissured specimens are highly dependent on the dynamic strain rate under same static pre-stress. Nevertheless, under same dynamic strain rate, the variation of the mechanical behavior of fissured specimens is not monotonous with increasing static pre-stress; the coupled strength and elastic modulus of fissured specimens feature an increase as the static pre-stress increases from 0 to 50% uniaxial compression strength ( σ c ), and then decrease when the static pre-stress ranging from 50% to 80% σ c . In view of energy principles, the fissured specimen with higher dynamic strain rate is characterized by more dissipated energy during the loading process and more released elastic energy at the end of loading under same dynamic strain rate. However, the greatest released elastic energy of fissured specimen occurs under the static pre-stress of 50% σ c . The splitting tensile failure is prominent in all recovered fissured specimens under coupled static-dynamic loads, and the two inner tips of preexisting fissures are coalesced with a typical tensile wing crack.